Current trends in treatment of uterine fibroids. A Perspective Review of Recent Literature - Bylica, Kinga; Dylewicz, Łukasz; Brzoza , Joanna; Rudzki, Jakub; Warmuz, Wojciech; Wystalska, Ewa; Solarz, Kacper; Czołpińska, Natalia; Kata, Zuzanna; Andrzejewicz, Jakub (Quality in Sport, 2026)
Uterine fibroids, or leiomyomas, are the most prevalent benign tumors in the female reproductive tract, affecting up to 70–80% of women by age 50. These tumors, which are composed of smooth muscle and connective tissue, often arise during the reproductive years and are influenced by a combination of genetic and hormonal factors. While many fibroids are asymptomatic, a significant number of women experience debilitating symptoms such as heavy menstrual bleeding, pelvic pressure, pain, and infertility, necessitating the need for effective treatment options. Historically, hysterectomy was the primary treatment; however, the desire for fertility preservation and advancements in medical technology have led to the emergence of minimally invasive and non-surgical treatment alternatives, including myomectomy, uterine artery embolization (UAE), and pharmacological therapies. Each treatment modality presents unique benefits and risks and should be tailored to individual patient factors, such as fibroid characteristics and reproductive goals. Despite the evolution of treatment options, awareness remains limited among patients, underscoring the need for enhanced patient education and shared decision-making in fibroid management. This review synthesizes current literature on the efficacy of various treatment strategies for uterine fibroids, highlighting the importance of personalized, evidence-based approaches to improve clinical outcomes and quality of life for women affected by this condition. This perspective review summarizes recent literature on current treatment options and trends, focusing on myomectomy, hysterectomy, embolization, and non-invasive techniques of uterine fibroids.